Efficacy of midwife-led role orientation of birth companions on maternal satisfaction and birth outcomes: a randomized control trial in Uganda - Eva Wodeya Wanyenze; Gorrette K. Nalwadda; Nazarius Mbona Tumwesigye; Josaphat K. Byamugisha (BMC, 2023)
Abstract Background The World Health Organization recommends birth companionship for all women in labor. There is insufficient evidence on birth companionship in low-income settings and it is not clear if role orientation impacts effectiveness. The aim of this study was to assess the efficacy of midwife-led role orientation of birth companions of on maternal satisfaction and birth outcomes in a sub-region in Uganda. Methods A stepped wedge cluster randomized trial conducted (control n = 240), intervention n = 235) from 4 clusters. Women who had a birth companion, in spontaneously established labor and, expecting a vaginal delivery were eligible. The intervention was "midwife-provided orientation of birth companions". The admitting midwife provided an orientation session for the birth companion on supportive labor techniques. The primary outcome was the chance of having a spontaneous vaginal delivery. Assessors were not blinded. Independent t-test and Chi-Square tests were used to assess the differences by study period. Results Mean maternal satisfaction rate was significantly higher in the intervention period compared to the control period (P > 0.001). High maternal satisfaction levels were noted among the women who were; at the regional referral hospital, younger, first-time mothers, and unmarried (P < 0.001). Satisfaction with pain management was rated lowest across study periods. Satisfaction with humaneness was rated highest with a higher score in the intervention period (93%) than the control (79.5%). There were no statistically significant differences in the mode of delivery, need to augment labor, length of labor and Apgar scores. Conclusion Midwife-led role orientation of birth companions increased maternal satisfaction. Nevertheless, no significant effect was noted in the mode of delivery, length of labor, Apgar score, and need to augment labor. Findings could inform the integration of birth companions in the admission process of the woman in labor in similar settings. Trial registration number NCT04771325.